Corrigendum: Identifying the link between serum VEGF and KL-6 concentrations: a correlation analysis for idiopathic pulmonary fibrosis interstitial lung disease progression - Zhong, Bin; Luo, Shuixiang (Frontiers in Medicine, 2024)
Background: Idiopathic pulmonary fibrosis interstitial lung disease (IPF-ILD) is a progressive lung disease characterized by excessive collagen deposition and lung fibrotic changes. Identifying reliable serum markers correlating with disease progression is crucial for diagnosis and prognosis. Objective: This study explored the association between serum markers KL-6 VEGF and IPF-ILD. Specifically, it assessed their correlation with PaO2, a measure of pulmonary gas function, to provide diagnostic and prognostic indicators. Methods: Patients with IPF-ILD were included, and their serum levels of KL-6 and VEGF were measured. Correlations with fibrotic damage and PaO2 were analyzed using statistical methods. The analysis confirmed a positive correlation between the serum marker KL-6 and the degree of fibrotic damage in IPF-ILD. On the other hand, the serum marker VEGF was found to promote disease progression. In terms of correlation with PaO2, both KL-6 and VEGF demonstrated high sensitivity and specificity. Specifically, the correlation between KL-6 and PaO2 suggests that it can be used as a reliable indicator to assess the status of pulmonary oxygenation function in patients with ILD. The correlation between VEGF and PaO2 helps to understand its role in the progression of IPF-ILD and provides an important basis for predicting patient prognosis. This study confirmed the correlation between KL-6 and VEGF with IPF-ILD and their association with PaO2. KL-6 and VEGF demonstrated high specificity and sensitivity in diagnosing, monitoring, and predicting prognosis in IPF-ILD. These findings contribute to our understanding of the disease and have clinical implications for diagnosis and prognostication.